Penerapan Terapi Spiritual Berdzikir pada Pasien dengan Halusinasi Pendengaran di Ruangan Indragiri RSJ Tampan Pekanbaru - Sri Hariyanti; Eka Malfasari; Ifon Driposwana Putra; Fitry Erlin (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Hallucinations are one of the symptoms of positive schizophrenia. Hallucinations are the loss of human ability to distinguish between internal stimuli (thoughts) and external stimuli (the outside world). One therapy that can be given to patients with auditory hallucinations is psychoreligious therapy. One of the most effective psychoreligions is dhikr, scientific evidence states that dhikr is a manifestation of a person's religious commitment. Psychoreligious therapy: dhikr by reading istighfar (Astaqfirullahal'adzim) 3 times, followed by tasbih (Subhannallah) 33 times, tahmid (Alhamdulillah) 33 times, and takbir (Allahu akbar) 33 times, this therapy is carried out for 3 days with a duration of 10-20 minutes. The purpose of this study was to explain Evidence Based Practice as a therapy for patients with auditory hallucinations using dhikr therapy. The implementation method used was the experimental technique (treatment) for patients with auditory hallucinations. The number of respondents needed was 2 people with a nursing diagnosis of auditory hallucinations. The study was conducted for 5 days, starting from April 23-28, 2025. Assessed using the Auditory Hallucination Rating Scale (AHRS) and SLKI questionnaires with a pretest and posttest testing process. The results of the study showed a decrease in pretest and posttest scores for performing dhikr spiritual therapy.